Informal caregiving in Singapore: macroeconomic realities and measures - Wayne Freeman Weien Chong (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2020)
The very rapid ageing of Singapore’s population is placing a huge burden on informal caregivers. I discuss two macroeconomic strategies – strengthening redistributive measures and professionalizing informal caregiving - that may alleviate this burden. A national study on informal caregiving is urgently required to identify specific areas and caregiver segments that will benefit from these strategies.